Distinguishing Delirium from Dementia - Malissa Mulkey; D. Erik Everhart; Sonya Hardin; Daiwai Olson; Cindy Munro (San Beda University, 2019)
Distinguishing between delirium and dementia is essential for understanding the underlying mechanisms which direct a nurse to the best interventions. However, delirium and dementia are conditions that are at times difficult to differentiate even for experienced clinicians. While the similarities can make distinguishing between the two disorders challenging, there are distinct differences. Therefore, this article describes similarities and differences in the characteristics of each condition to assist clinicians in accurate detection and identification.